Factors Influencing Relapse After Omalizumab in Chronic Urticaria. Does the Method of Discontinuation Influence Relapse? - Petek Üstün; Esra Adışen (Dermatology Practical & Conceptual)
Introduction: Omalizumab is recommended until spontaneous remission occurs rather than for a specific period of time in chronic urticaria (CU). The rate of recurrence of symptoms after treatment varies depending on the method of discontinuation.